Educação infantil: reflexões sobre a trajetória de uma educadora - MACHADO, Gerbziane Cléia Bahia (2023)
The present work is an autobiographical study whose theme is “CHILD EDUCATION: reflection on the trajectory of an educator”. This memorial aims to reflect on my trajectory as an educator of Early Childhood Education, in the municipality of Gurupá/PA, highlighting my personal and professional life trajectory. In order to achieve the proposed objectives, the research is divided into four sections: the first emphasizes the memories of my childhood and my family, in the second moment: reflection of my trajectory as a student, in the third abortion my professional experience and fourth I reflect on the PARFOR. As a methodology, autobiographical research was adopted, which according to Gil (2002) allows the researcher to describe facts and relate them to the theme addressed. Bibliographical research, which according to Gil (2002), brings investigation into various documentary sources as an investigation, was used in this work as a way of seeking theoretical contributions, to enable a qualitative reflection of the narrative made which, according to Minayo (2001), Qualitative approach works with the universe of meanings, motives, aspirations, beliefs, values and attitudes, which in this case will serve as a source of reflection on my life and professional trajectory. Tardif (2003), Freire (1996), Àries (2006), among others, were used as a theoretical reference, which will remain in dialogue with the chosen theme and my historical trajectory of life and professional training. The research made it possible to reflect on my experience as a teacher in early childhood education, allowing me to realize that the pedagogical work in preschool goes far beyond the simple act of caring, and the educator must constantly reflect on his pedagogical practice.